The Validation of Local Knowledge-Based Module (LKBM) as Character Development Modul for Elementary School Students in Kupang, Indonesia - Uslan Uslan; Mega M Saleh; Bilam S Linome (Postgraduate, University of Mataram, 2023)
The purpose of the current research was to validate the local knowledge-based module (LKBM) to elementary school student character in Kupang, Indonesia. The participants of the current research were 78 elementary school students in Kupang, Indonesia. This research is quasi-experimental, utilising descriptive analysis and MANOVA to analyse the data. Therefore, the students were divided into a control group (n = 39) and an experiment group (n = 39). Based on the results, the module was valid and reliable to be used as learning material for character education. It was proved through the improvement in the students character development before, during, and after the use of the module. Other than that, MANOVA analysis proved significant in the students character who follow the learning process with the Local Knowledge-Based Module (LKBM) compared to the group of students who use conventional learning. Therefore, it can be concluded that the module can be used in character education learning process.